1998
DOI: 10.3109/00207459808986466
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunctions in Children with Attention Deficit Hyperactivity Disorder

Abstract: One hundred and twenty-four male children ranging in age from seven to 12 years-old were selected. The sample was divided into two groups: (1) sixty-two with attention deficit hyperactivity disorder (ADHD) children; and (2) sixty-two normal matched controls (N-ADHD). Three tests were individually administered: (1) Wisconsin Card Sorting Test (WCST); (2) Verbal fluency and semantics (animals and fruits); and, (3) Picture Arrangement subtest of the WISC-R. For all the test scores, statistically significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 55 publications
3
47
0
8
Order By: Relevance
“…Only when tasks represent complex problems that require voluntary and programmed behavior with internal control (executive function) will children with ADHD fail. The question is that not all executive standard tests are really problems for all children (Pineda et al, 1999e;Pineda et al, 1998;Westby & Cutler, 1994). Using a standard questionnaire for ADHD conduct (Chang & Chuang, 2000), a screening ADHD prevalence of 14.1% in adolescents from high schools was found.…”
Section: Discussionmentioning
confidence: 98%
“…Only when tasks represent complex problems that require voluntary and programmed behavior with internal control (executive function) will children with ADHD fail. The question is that not all executive standard tests are really problems for all children (Pineda et al, 1999e;Pineda et al, 1998;Westby & Cutler, 1994). Using a standard questionnaire for ADHD conduct (Chang & Chuang, 2000), a screening ADHD prevalence of 14.1% in adolescents from high schools was found.…”
Section: Discussionmentioning
confidence: 98%
“…In prior research, this measure had been sensitive to differences between students with and without ADHD specifically on the subtests of trials to criterion, number of categories identified, errors, and conceptual level responses (e.g., Boucugnani & Jones, 1989;Pineda et al, 1998). Replicating past research, this sample of students with attentional deficits required more trials to criterion (i.e., referring to Total Number Correct on the WCST) than did the comparisons.…”
Section: Discussionmentioning
confidence: 94%
“…The WCST provides a measure of sorting and problem solving activity. In addition to good reliability (range r=.91-.96; Axelrod & Henry, 1992), this test has been shown to differentiate between students with ADHD and typical students in problem solving, learning, visual spatial, and categorization abilities (Boucugnani & Jones, 1989;Chelune, Ferguson, Koon, & Dickey, 1986;Pineda et al, 1998). The WCST was given after the experiment so that it would not confound the effects of the conditions and would provide an assessment of generality of the conditions.…”
Section: Wisconsin Card Sorting Test (Wcst)mentioning
confidence: 98%
See 1 more Smart Citation
“…The task is clearly not selectively affected by frontal lobe lesions (Warrington, James, & Maciejewski, 1986), although to be honest, virtually no such test exists. Nevertheless, the Picture Arrangement subtest of the WISC has indeed been found to be sensitive to ADHD (Pineda et al, 1998). Even fathers of ADHD children seem to have low performance on this subtest (Casey, Cohen, Schuerholz, Singer, & Denckla, 2000).…”
Section: Methodological Considerationsmentioning
confidence: 98%